2021
DOI: 10.1177/09636625211002375
|View full text |Cite
|
Sign up to set email alerts
|

Masculinity in the public image of physics and mathematics: a new model comparing Japan and England

Abstract: Women are a minority in science, technology, engineering and mathematics academic careers. In particular, few women in Japan choose to study physics and mathematics. In this study, we investigated the factors contributing to the masculine image of physics and mathematics based on the framework of our expanded model. We conducted online questionnaire surveys in Japan and England, and found that physics and mathematics occupations, and mathematical stereotypes were both related to a masculine image. Only in Japa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…It is important to acknowledge that biases differ between cultures. A recent study that compared physics- and mathematics-related stereotypes between Japan and the United Kingdom found that in Japan (but not in the United Kingdom) a person’s attitude to intellectual women was related to viewing mathematics as “masculine,” but “the experience of being told or having heard that the choice of a particular course of studies would make someone less attractive to the opposite sex was evident only in England” ( Ikkatai et al, 2021 : 810). However, the results we describe here, that suggest that female scientists receive more negative feedback when writing in a more popular language, seem to hold true across English-speaking and Hebrew-speaking popular science.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to acknowledge that biases differ between cultures. A recent study that compared physics- and mathematics-related stereotypes between Japan and the United Kingdom found that in Japan (but not in the United Kingdom) a person’s attitude to intellectual women was related to viewing mathematics as “masculine,” but “the experience of being told or having heard that the choice of a particular course of studies would make someone less attractive to the opposite sex was evident only in England” ( Ikkatai et al, 2021 : 810). However, the results we describe here, that suggest that female scientists receive more negative feedback when writing in a more popular language, seem to hold true across English-speaking and Hebrew-speaking popular science.…”
Section: Discussionmentioning
confidence: 99%
“…There has been research into the gender problem in STEM, ranging from the varied perception that certain fields are too masculine, to negative stereotypes about female abilities, to the lack of diversity in representations of female (Ikkatai et al, 2021) and other minorities. These problems are connected to local cultural expectations and beliefs of the place including how smartness is gendered.…”
Section: Literature Reviewmentioning
confidence: 99%